Insights into microfabrication and implementation of microfluidics in pharmaceutical drug delivery and analysis - Omnia A. Al-wdan; Omnya A. Sharallah; Nada A. Abdelwahab; Alshimaa O. Mohammed; Enas Elmowafy; Mahmoud E. Soliman (Elsevier, 2023)
Microfluidics are systems that set forth valuable means to efficiently control fluid movement and dynamics in specially fabricated micro-channel systems. The advancement of the unique design and microfluidics technology can offer an alternative to the traditional systems used in many pharmaceutical applications. In this context, this review presents a vivid depiction of microfluidics and an overview of the various mixing techniques and mechanisms. Insights on how microfluidic methodologies can be utilized in the efficient manufacture of various drug delivery systems e.g., liposomes, microparticles, nanoparticles, and nano-in-microparticles are provided. Moreover, the different analytical applications of microfluidic systems such as lab-on-chip, dielectrophoresis, droplet microfluidic, and digital microfluidics are addressed. Specifically, the pharmaceutical approaches for antibody screening technology and Cell-free protein synthesis system are highlighted. Lastly, the modular microfluidic approach in planning and constructing microfluidic systems is explored as a key player for implementing futuristic custom-made microfluidic systems. Collectively, microfluidic systems hold the potential in various domains including biosensors, point-of-care diagnostics, health monitoring and patient care management.